DESEMPENHO DE CULTIVARES DE BATATA EM SISTEMA ORGÂNICO: CRESCIMENTO, PRODUTIVIDADE E RESPOSTA A REQUEIMA E A LARVA ALFINETE - PASSOS, SARA (2016)
This work has the objective of evaluate the growth, yield, late blight severity and San Antonio beetle larvae damage in potato cultivars in organic system in the South of Brazil. It were realized three trials, in the crop season 2013 and 2014, in Guarapuava-PR and Caseiros-RS. The cultivars utilized were: „Ágata‟ (control), „BRS Clara‟, „BRS Eliza‟, „EPAGRI 361-Catucha‟, „IPR Cris‟, „IAC Aracy Ruiva‟ and „IAC Vitória‟. It were evaluated the growth, light absorption, yield and yield components, late blight severity in leaves and San Antonio beetle larvae damage in tubers. The experiment design was a randomized block in a split plot scheme, with trials as main plot and cultivars as subplot, with four repetitions. „EPAGRI 361-Catucha‟ had higher leaf area index, tuber initiated, tuber formed, tuber dry matter and total dry matter, in addition to show higher solar radiation absorption, at the initial growth stage, than the other cultivars. Cultivars total and marketable yield varied according to the trials, but, „EPAGRI 361-Catucha‟ stayed in the group of cultivars with highest yield, with average of 28 t ha-1 of total tuber yield, and with higher percentage of tuber dry matter, at all three trials. „Agata‟ showed the highest susceptibility to late blight in two trials and „BRS Clara‟ the lowest susceptibility. The higher number of damage holes of San Antonio beetle larvae on the tubers was observed in „IAC Vitoria‟ and „BRS Eliza‟, and the cultivars „EPAGRI 361-Catucha‟ and „IPR Cris‟ had the lowest percentage of damage on the tubers. The cultivar „EPAGRI 361-Catucha‟ can be recommended for organic cultivation in the South of Brazil, because of its high growth and development, in addition to high yield and low tubers damage.